Development of an anti-pollution coating process technology for the application of an on-site PV module - Jung, Sejin; Choi, Wonseok; Kim, Jung Hyun; Ko, Jang Myoun (Beilstein Journal of Nanotechnology, 2019)
This study aimed to apply annealing processes during the coating of photovoltaic (PV) module glasses to PV modules already installed through an easy and simple procedure. Three types of annealing treatments were applied to PV module glasses, i.e., furnace, rapid thermal annealing (RTA) and torch. Among these, torch annealing, which can be easily carried out at PV module installation sites, was applied to PV module glasses using different numbers of repetition. Light transmittance, contact angle, anti-pollution characteristics, adhesion and hardness of the functional coating films after using different annealing treatment times and methods were measured, and it was confirmed that these characteristics varied depending on the annealing treatment times and methods. Through this, it was possible to optimize the process conditions that provide excellent anti-pollution characteristics and could be easily utilized at on-site PV modules.
Keywords: annealing; anti-pollution; functional film; gas torch; PV module

(untitled) - Tyagi, V. V.; Rahim, N. A. A.; Rahim, N. A.; Selvaraj, J. A. (Renewable Sustainable Energy Rev., 2013)

(untitled) - Cao, F.; Chen, K.; Zhang, J.; Ye, X.; Li, J.; Zou, S.; Su, X. (Sol. Energy Mater. Sol. Cells, 2015)

(untitled) - Li, X.; Zhou, Y.; Xue, L.; Huang, L. (Technol. Forecast. Soc. Change, 2015)

(untitled) - Liu, C.; Zhang, X.; Li, J.; He, Y.; Li, Z.; Li, H.; Guo, W.; Xie, W. (Synth. Met., 2015)

(untitled) - Isshiki, M.; Sichanugrist, P.; Abe, Y.; Oyama, T.; Odaka, H.; Konagai, M. (Curr. Appl. Phys., 2014)

(untitled) - Yu, W.; Shen, L.; Shen, P.; Meng, F.; Long, Y.; Wang, Y.; Lv, T.; Ruan, S.; Chen, G. (Sol. Energy Mater. Sol. Cells, 2013)

(untitled) - Shan, B.; Kang, H.; Choi, W.; Kim, J. H. (Trans. Electr. Electron. Mater., 2017)

(untitled) - Park, J. T.; Kim, J. H.; Lee, D. (Nanoscale, 2014)

(untitled) - Joung, Y.-H.; Choi, W. S.; Shin, Y.; Lee, M.; Kim, H.; Song, W. (J. Korean Phys. Soc., 2013)